Environmental Quality and Ecological Risk Assessment of Heavy Metals in the Zhuhai Coast, China - Wu, Jin; Rong, Shaowei; Wang, Miaowei; Lu, Rong; Liu, Jingchao (Frontiers in Marine Science, 2022)
The rapid urbanization and industrialization in the coastal Zhuhai have resulted in severe heavy metal contamination. Heavy metals are extensively used as indicators of coastal contamination, but the comparability among different geographic environments needs to be further explored and scrutinized. In this study, heavy metals (i.e., As, Zn, Cd, Cr, Hg, Cu, and Pb) in surface seawater (20 sites), sediments (10 sites), and organisms (13 sites, shellfish, algae, fish, and crustaceans) were analyzed to assess the distribution, enrichment, and ecological risk in the coastal regions of Zhuhai (2017 and 2018). The results showed that Cu, Zn, and Pb exceeded the standards of seawater, indicating the presence of anthropogenic pollution. Meanwhile, the ecological risk results showed that Cd and Cu indicated moderately high environmental risks. The quantity and quality of heavy metals in organisms showed different trends in the sea, which affected marine organisms in the northeastern area. The main factors contributing to the ecological risk of these two heavy metals are the emissions from chemical companies. Therefore, preserving the high biological diversity in this area is important to ensure the health and productivity of the seawater ecosystem in the coastal area. These results may play a key role in promoting decision makers to manage the sustainability of the Zhuhai coast.